2022
DOI: 10.1002/lno.12261
|View full text |Cite
|
Sign up to set email alerts
|

A positive temperature‐dependent effect of elevated CO2 on growth and lipid accumulation in the planktonic copepod, Calanus finmarchicus

Abstract: Calanus finmarchicus were reared from eggs to adults at 12 C and 16 C with non-limiting food in combination with ambient (600 μatm) and high (1100 μatm) pCO 2 . These conditions are likely to be encountered by the species at the southern margins of its biogeographical range by the end of the century. Dry weight (DW), carbon (C) and nitrogen (N) mass, oil-sac volume (OSV), fatty acid composition (FA), and oxygen consumption rates (OCR) were measured on newly molted stage CV copepodites and recently molted adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Interestingly, variance among sampling sites increased over time, indicating differences in recovery capacity and stressing the need for long-term observations. The results of Lange et al (2023) emphasizing species-specific differences in responses parallel the findings of several other studies documenting speciesspecific physiology and behavior in zooplankton, including Bomfim et al (2023), Carrier-Belleau et al (2023, Ramondenc et al (2023), andFields et al (2023), documenting zooplankton species specific physiology and ecology. Similarly, Meyer-Gutbrod et al (2023) showed that right whale pod identity is critically important, and Su et al (2023) concluded that location and species were critical to the differential results in their aquaculture lake study.…”
Section: Biological Details Mattersupporting
confidence: 80%
See 4 more Smart Citations
“…Interestingly, variance among sampling sites increased over time, indicating differences in recovery capacity and stressing the need for long-term observations. The results of Lange et al (2023) emphasizing species-specific differences in responses parallel the findings of several other studies documenting speciesspecific physiology and behavior in zooplankton, including Bomfim et al (2023), Carrier-Belleau et al (2023, Ramondenc et al (2023), andFields et al (2023), documenting zooplankton species specific physiology and ecology. Similarly, Meyer-Gutbrod et al (2023) showed that right whale pod identity is critically important, and Su et al (2023) concluded that location and species were critical to the differential results in their aquaculture lake study.…”
Section: Biological Details Mattersupporting
confidence: 80%
“…Even different life cycle stages of the same species responded uniquely to environmental drivers. Fields et al (2023) found differences in copepod responses at different developmental stages when subject to manipulated temperature and pCO 2 treatments. These life‐stage specific differences have direct implications for the nutritional value of these zooplankton to higher trophic levels.…”
Section: Biological Details Mattermentioning
confidence: 99%
See 3 more Smart Citations